DIFFERENTIAL COSTS. - Saliers, E. A. (The Accounting Review, 1943)
The article focuses on the differential cost that occurs when the manufacturer changes the quantity of its production. A manufacturer may wholly or partly avoid spoiling the market by selling his increments in output abroad, or by appealing to a different domestic market from the one in which he has been disposing of his goods. According to some theories if additional production results in lower prices for all units, true differential cost must include the loss resulting from such price reduction. Since differential costs are anticipated costs, they do not enter into the accounts. The author in this article considers the theory which underlies differential costs. A brief outline of practical procedure suitable for the accumulation of available factual data is presented, including suggestions as to how statistical forecasts of costs at various anticipated levels of production can be made. Various assumptions are sometimes made relative to cost trends at stated levels of future production. One such assumption is that differential costs will be less with each increased level of production until full capacity production is reached.